Integrity Assessment of Shipping Line Pipelines Using Risk-Based Analysis to Determine Risk and Maintenance Strategies - Anggraini, Ade Ratih; Nurjaya, Dwi Marta (Journal of Materials Exploration and Findings, 2025)
Pipeline Shipping Lines X, Y & Z are classified as critical infrastructure, being the only transportation through the crude oil lifting from P and R location to the transfer station in NM Area. To maintain the workflow of the Shipping Line, integrity assessments and risk evaluation are required to ensure the operational and safety. Anomalies were found by analysing inspection, monitoring, and repair data, while the pipelines' future integrity was assessed by calculating the remaining life. Risk-Based Analysis (RBA), which is a modification of Kent Muhlbaeur's method, is employed to conduct the risk assessment using the Probability of Failure (POF) and Consequence of Failure (COF) in order to develop the risk profile. Simulations of pressure built up, temperature drop, and wax deposition are performed through flow assurance analysis to predict the Shipping Line condition. The results of the integrity assessment show that the Shipping Lines X, Y, and Z is fit-for-service. Nevertheless, some concerns need to be addressed, including active internal degradation mechanisms such as Under Deposit Corrosion (UDC) and Microbiologically Induced Corrosion (MIC), as well as active external threats such as Corrosion Under Insulation (CUI). The result of integrity and risk assessment Shipping Lines X, Y, and Z are crucial for planning inspection schedules and maintenance strategies in short, medium, and long term.